Vitamin D supplementation and breastfeeding. Issue 5 (May 2017) - Mounsey, Anne
Abstract : N/A: Hollis BW, Wagner CL, Howard CR, et al. Maternal versus infant vitamin D supplementation during lactation: a randomized controlled trial. Pediatrics . 2015; 136(4):625–634.